Perceived insecurity, mental health and urbanization: Results from a multicentric study. (May 2016) - Luciano, M; De Rosa, C; Del Vecchio, V; Sampogna, G; Sbordone, D; Atti, AR; Bardicchia, F; Bertossi, F; Calò, S; Cava, L; Ciafone, M; De Fazio, P; et al.
Aims: This article aims to (1) explore the levels of perceived insecurity in a sample of patients with mood or anxiety disorders and (2) assess whether living in 'big cities' can influence the levels of patients' perceived insecurity and social contacts compared to living in a non-urbanized context. Methods: A total of 24 Italian mental health centers (MHCs) have been invited to participate. Twenty patients consecutively accessing the MHC have been recruited. All patients have been assessed using validated assessment tools. Results: The sample consisted of 426 patients, mostly female, with a mean age of 45 years. Globally, 52.2% of patients had a diagnosis of mood disorders, and 37.8% had anxiety disorders. Half of the sample declared that the main feeling toward life is uncertainty; higher levels of pessimistic views toward life have been detected in patients living in urban areas. A positive association between negative attitudes toward life and higher levels of depressive and anxiety symptoms, poor social functioning and higher levels of perceived psychological distress has been found. Conclusion: Our findings confirm the presence of a common sense of perceived uncertainty among our sample. Such attitude toward life can have a detrimental impact on patients' psychological and physical well-being, contributing to high levels of distress.